(untitled) - Wyatt, Rawdon (Harlow, 2002)
*58 photocopiable activities that focus on the key skills needed for success in the examination *Wide variety of enjoyable and practical activities that will familiarise students with the exam format *Detailed teacher's notes giving step-by-step instructions, follow-up suggestions, timing of activities and full answer keys *Quick reference contents page showing the activity focus, activity type, time and preparation required *Most activities can be completed in 15-30 minutes
Keywords: English language; Textbooks for foreign speakers